2010
DOI: 10.1523/jneurosci.0404-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Attentional Modulation of Local Field Potential Signals in Macaque Area MT

Abstract: Visual attention modulates neuronal responses in primate motion processing area MT. However, whether it modulates the strength local field potentials (LFP-power) within this area remains unexplored, as well as how this modulation relates to the one of the neurons' response. We investigated these issues by simultaneously recording LFPs and neuronal responses evoked by moving random dot patterns of varying direction and contrast in area MT of two male monkeys (Macaca mulatta) during different behavioral conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 54 publications
(89 reference statements)
9
45
1
Order By: Relevance
“…A recent study (Khayat et al 2010) showed that LFP spectral power in the beta band is attenuated when attention is directed to MT (see also Harris and Thiele 2011;Lee et al 2013). It could account for several DP trends if, after detecting the motion pulse, the monkey focused more attention on the visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study (Khayat et al 2010) showed that LFP spectral power in the beta band is attenuated when attention is directed to MT (see also Harris and Thiele 2011;Lee et al 2013). It could account for several DP trends if, after detecting the motion pulse, the monkey focused more attention on the visual stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…A change in attention could also explain why high-gamma LFP-DP increased late in the trial, as this band is known to respond to changes in attention (Fries et al 2001;Khayat et al 2010;Rotermund et al 2009;Womelsdorf et al 2006; but see Ray and Maunsell 2011a) and possibly perceptual state (Panagiotaropoulos et al 2012). Since the beta and gamma bands respond differently to attention signals in MT (Khayat et al 2010) and because late beta LFP-DP had no pairwise correlation with high-gamma LFP-DP (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LFP response to a given stimulus condition was taken as ⌬R averaged over the gamma band (25-90 Hz), which has been widely studied (Pesaran et al, 2002;Henrie and Shapley, 2005;Viswanathan and Freeman, 2007;Katzner et al, 2009) and found to be highly tuned to visual stimuli (Frien et al, 2000;Henrie and Shapley, 2005;Liu and Newsome, 2006;Berens et al, 2008;Khayat et al, 2010). Data analyses.…”
Section: Methodsmentioning
confidence: 99%
“…These analyses provide valuable information to study brain structures and functions in a more precise manner. As cases in point, it has been employed in the following studies: (1) decoding spoken words using LFP in cortical surface (Kellis et al 2010), (2) modulation of LFP by contrast, and the direction of motion in medial temporal (MT) (Khayat et al 2010), (3) tuning LFP for speed, direction and observation of high correlation in certain frequencies, especially the gamma band in the MT area (Liu and Newsome 2006), (4) decoding dexterous finger movements using LFP in M1 (Mollazadeh et al 2008), (5) decoding hand movement using LFP in motor cortex (Mehring et al 2003), and (6) application of LFP in decoding of stimulus-reward pairing in V4 of monkeys (Manyakov et al 2010).…”
Section: Introductionmentioning
confidence: 99%